TIPE PEMISAHAN DAN PENGARUHNYA TERHADAP LABA PADA BANK UMUM SYARIAH HASIL PEMISAHAN - M Nur Rianto Al Arif; Ismawati Haribowo (Jurnal Keuangan dan Perbankan, 2016)
The aim of this research is to analyze if there is a difference between the spinoffs type and profit at spinoffs bank. There are two type of spinoff in Indonesian Islamic banking industry, such as: spinoff that using acquisition, convert, merger and spinoff; and; pure spinoff. This research is using panel regression with random effect. The result shows there is no difference between type of spinoff and operational profit at spinoffs bank. This result implies that the spinoff type is decided according the business strategy that are going to choose by the parents bank. There are a lot of factors that are going to be considered to choose the spinoffs type for separate the Islamic business unit from its parents bank.